Beyond the Ledger: How Online Culinary MSMEs Around Campuses Weave Social and Environmental Care into Their Business - Aep Saefullah; Liza Nora; Andry Priharta (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study investigates how digital-based culinary micro, small, and medium enterprises (MSMEs) located around university campuses incorporate sustainability accounting practices into their daily operations and financial management. The research adopts a mixed-method approach with a sequential explanatory design, combining quantitative survey data from 120 MSME owners and consumers with qualitative insights from in-depth interviews. The findings reveal that digital integration—particularly through online platforms and digital payment systems—has significantly enhanced operational efficiency and market reach. However, the adoption of sustainability accounting remains limited. Quantitative results indicate that fewer than 40% of MSMEs apply structured cost management practices, and less than 30% engage in environmentally oriented initiatives. Qualitative findings further highlight key constraints, including limited financial literacy, restricted access to green financing, and low awareness of environmental responsibility. Despite these challenges, MSMEs demonstrate emerging informal practices that reflect social and environmental concern, particularly through community engagement and waste reduction efforts. These hybrid practices suggest the presence of latent sustainability potential that has not yet been formalized into systematic accounting frameworks. This study contributes to the literature by extending the discourse on sustainability accounting to the context of digital culinary MSMEs in campus-based ecosystems. Practically, the findings provide policy-relevant insights for strengthening sustainability-oriented capacity building, developing accessible green financing schemes, and fostering collaboration among MSMEs, universities, and local governments to support inclusive and sustainable business transformation.